Thiol-functionalized cellulose nanofiber membranes for the effective adsorption of heavy metal ions in water. (15th April 2020) - Choi, Hyeong Yeol; Bae, Jong Hyuk; Hasegawa, Yohei; An, Sol; Kim, Ick Soo; Lee, Hoik; Kim, Myungwoong
Highlights: Thiol functionalization on cellulose nanofiber surface imparting ability to adsorb metal ions. Adsorption occurring only on the surface with homogeneously distributed adsorption energy. Kinetic studies revealing the role of surface thiol in metal ion adsorption mechanism. Expandability of cellulose for biocompatible, nontoxic, and sustainable water purification membrane applications. Abstract: This work reports the fabrication of a thiol-functionalized cellulose nanofiber membrane that can effectively adsorb heavy metal ions. Thiol was incorporated onto the surface of cellulose nanofibers, which were fabricated by the deacetylation of electrospun cellulose acetate nanofibers and subsequent esterification of a thiol precursor molecule. Adsorption mechanism was investigated using adsorption isotherms. Adsorption capacity as a function of adsorbate concentration was described well with Langmuir isotherm, suggesting that metal ions form a surface monolayer with a homogenously distributed adsorption energy. Maximum adsorption capacities in the Langmuir isotherm for Cu(II), Cd(II), and Pb(II) ions were 49.0, 45.9, and 22.0 mg·g −1, respectively. The time-dependent adsorption capacities followed a pseudo-second-order kinetic model, suggesting that chemisorption of each doubly charged metal ion occurs with two thiol groups on the surface. These results highlight the significance of surface functionality on biocompatible, nontoxic, and sustainable cellulose materials to expand their potential and applicability towards water remediation applications.